Mild obesity, physical activity, calorie intake, and the risks of cervical intraepithelial neoplasia and cervical cancer. - Jae Kwan Lee; Kyeong A So; Chandrika J Piyathilake; Mi Kyung Kim (PLoS ONE, 2013)
OBJECTIVE: We investigated whether obesity, physical activity, and calorie intake are associated with the risks of cervical intraepithelial neoplasia (CIN) and cervical cancer. METHODS: We enrolled 1125 women (age, 18-65 years) into a human papillomavirus cohort study established from 2006 to 2012. Multinomial logistic regression models were used to estimate crude and multivariate odds ratios (ORs) and the corresponding 95% confidence intervals (95% CIs), and to assess whether body mass index (BMI), height, weight, total calorie intake, and physical activity were associated with the risks of CIN and cervical cancer. RESULTS: Cervical cancer risk was positively associated with BMI and inversely associated with physical activity. When compared with women with a normal BMI (18.5-23 kg/m(2)), the multivariate ORs (95% CIs) for those overweight (23-25 kg/m(2)) and mild obesity (≥25 kg/m(2)) were 1.25 (0.79-2.00) and 1.70 (1.10-2.63), respectively. When compared with women with the lowest tertile of physical activity (<38.5 MET-hours/week), the ORs (95% CIs) for cervical cancer were 0.95 (0.61-1.48) and 0.61 (0.38-0.98) for women with medium physical activity (38.5-71.9 MET-hours/week) and those with high physical activity (72 MET-hours/week), respectively (p for linear trend  = 0.03). The CIN2/3 risk was inversely associated with physical activity after adjustment for confounders. Compared with women with low physical activity (< 38.5 MET-hours/week), the ORs (95% CIs) for CIN2/3 were 0.64 (0.40-1.01) and 0.58 (0.36-0.93) for the medium and high physical activity groups, respectively (p for linear trend  = 0.02). Total calorie intake was not statistically associated with the risks of CIN and cervical cancer after adjustment for confounders. CONCLUSION: Our results indicate that in addition to screening for and treatment of CIN, recommendations on the maintenance of an appropriate BMI with an emphasis on physical activity could be an important preventive strategy against the development of cervical cancer.